A PROBLEM OF QUALITY OF INVENTORY MEDICAL STORES FOR MILITARY HOSPITALS - A. G. Golub; N. I. Khomutetskaya (Фармация и фармакология (Пятигорск), 2015)
The article is devoted to problems of inventory medical stores optimization for rendering medical care in military hospitals with due regard for qualities of products of inventory medical property.